Nanoparticle Delivery in Microvascular after Cerebral Ischemia: A Simulation Study - Peiqian Chen; Bing Dong; Weiwu Yao (Applied Bionics and Biomechanics)
Nanodrug delivery systems have been used in the diagnosis and treatment of ischemic stroke. However, the delivery mechanisms of nanoparticles within microvascular after cerebral ischemia have not been systematically revealed. This study aims to investigate the binding of different nanoparticles to the walls of ischemic brain microvascular through numerical simulations. In this study, 3D models of cerebral microvascular based on ischemic pathological changes are constructed. After building the mesh of microvascular, computational fluid dynamics is used to simulate blood flow and nanoparticle delivery. The simulation results show that the total amount of binding nanoparticles with small size is higher than that with large size. The large-sized nanoparticles are more easily delivered to the stenosis. The density of the nanoparticles has no significant effect on delivery. Furthermore, the study finds that the presence of red blood cells can significantly enhance the delivery efficiency of nanoparticles. In addition to evaluating the forces exerted on the nanoparticles, the impact of the binding affinity of the modified ligand on nanoparticles to the target receptor on delivery is investigated. In summary, selecting suitable nanoparticles according to different targets will improve the delivery efficiency of nanodrugs. The microvascular delivery model of nanoparticles proposed in this study may be helpful in the design of nanoparticles for diagnosis and treatment of cerebral ischemia.